A Handbook of reflective and experimental learning: theory and pactice - Moon, Jennifer (New York: Harvard Education Press, 2005)
Contents: A generic view of learning. Exploring reflective and experimental learning. Working with reflective and experiential learning.
Include appendix
Keywords: Active Learning